The Role of Temple as a Cultural Learning Source - กตปุญฺโญ, พระครูโสภิตปุญญากร; โอภาโส, พระครูโอภาสนนทกิตติ์ (Journal of Educational Review Faculty of Education in MCU, 2018)
The first Buddhist temple is Valuvana Temple built by King Bimbisara in Magadha State of ancient India. This temple can interest and bring Buddhists around the world to visit and earn a lot of income to India. The learning resources in temples from the ancient time to present that were created in the forms of fine arts, sculpture and architecture were to propagate Buddhist teachings and the mental centers of Buddhists. At present, the trend of cultural tourism is increasing. Buddhist temples are the best cultural learning resources of visitors.